A Usul al-Fiqh Study of the Imperative (Amr) and Its Legal Implications in Qur’anic Verses and Hadith: An Analysis of Contemporary Fiqh - Jumriani J; Fatmawati F; Muh. Nur Taufiq Sunusi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The study of the term Amar (command) is one of the important topics in ushul fiqih, as determining the meaning of syar’i law largely depends on the understanding of commands found in the Qur'an and Hadith. Experts have differing views on whether the term Amar indicates an absolute obligation, merely a recommendation, or just permission. This article aims to explore the foundation of the term Amar, its application in verses and Hadith, and its legal implications in the context of modern fiqih. The research method used is literature review with a textual and contextual analysis approach. The results show that most ushul scholars agree that the term Amar essentially indicates obligation, unless there is a qarinah that diverts that meaning. However, in modern fiqh, the legal impact of Amar is greatly influenced by maqasid al-shariah and social situations. This emphasizes that the understanding of Amar needs to be flexible while still being grounded in the principles of classical ushul fiqh.